PERSEPSI SANTRI TERHADAP BANK SYARIAH - ANY MEILANI (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2017)
The theme of the article is "economy based on the principles of Islam". The purpose of this research is to identify the santri perception toward syaria bank and to analyze the perception of santri between pesantren one with other pesantren. The location of the research was conducted in three locations, namely Darunnajah Pesantren, Pesantren Daar El-Qolam and Pesantren Darul Amanah. The sample of the research is santri of 120 people, taken by simple random sampling from each pesantren counted 40 people by using questioner. The questionnaire contains the profiles and perceptions of santri towards sharia banks. To analyze the santri's perception level in general and to compare the santri perception level between pesantren one with other pesantren using Factor Analysis with Lisrel 8,54. The results showed that: 1) The level of perception of santri against Islamic banks is proportionally equal. The level of perception is almost owned by students (47.5%), perceptions good and very good (44.1%), and less (8.3%). This shows that students in pesantren have a good perception about syariah bank; 2). The perception of santri towards Islamic banks in three different levels of pesantren. The highest levels of students' perceptions are the Darunnajah Pesantren, the Daar El-Qolam Pesantren, and the Darul Amanah Pesantren. For the future, sharia banks should conduct socialization to pesantren because pesantren is a big potential for the development efforts of sharia banks in Indonesia.